Growth and secondary metabolites content of chloroform extract of Chlorella sp. and Chlorella sorokiniana cultured on chicken broiler waste media - Devy Susanty; Ade Ayu Oksari (Smujo International, 2020)
Abstract. Susanty D, Oksari AA. 2020. Growth and secondary metabolites content of chloroform extract of Chlorella sp. and Chlorella sorokiniana cultured on chicken broiler waste media. Nusantara Bioscience 12: 28-32. Intensive chicken broiler farms create waste in the environment. Chicken Broiler Waste (CBW) was used as culture media for Chlorella sp. InaCC M39 and Chlorella sorokiniana InaCC M38 at various concentrations (2, 4, 6, 8, and 10%), and compared to AF6 media. The growth of Chlorella was observed every 48 hours for 10 days by counting the number of cells using a hemocytometer. The chloroform extract of Chlorella sp. and C. sorokiniana were analyzed for their phytochemical content to determine the presence of alkaloids, flavonoids, saponin, steroids, and tannin. The results showed that 2% of CBW media was the best medium for the growth of Chlorella with nitrogen (N), phosphorus (P), and potassium (K) content was 0.01% N; 0.01% P; 0.06% K respectively. The highest specific growth rate of Chlorella sp. on 2% CBW medium was on the 8th day of culture (0.8133) with cell density of 1.6 x 106 cells/mL, while the highest specific growth rate of Chlorella sorokiniana was on the 6th day (0.8907) with cell density of 2.99 x 107 cells/mL. The chloroform extract of the biomass of Chlorella sorokiniana contained steroid and saponin